Մեղրախոտի (Stevia rebaudiana Bertoni) լեյկոպոեզ խթանող ազդեցությունը սակավաշարժության դինամիկայում - Ծ. Ի. Ադամյան; Ս. Մ. Մինասյան; Է. Ս. Գևորգյան; Յու. Լ. Ջհանգիրյան; Է. Ս. Ղուկասյան; Հ. Մ. Կարապետյան (ՀՀ ԳԱԱ հրատ.)
Исследован характер изменения морфофункциональных показателей лейкопоэза в динамике комплексного воздействия гипокинезии и листьев стевии. Показано, что содержащиеся в листьях стевии биологически активные вещества, активизируя процессы пролиферации и созревания клеток лейкобластного ростка, блокируют отрицательное влияние гипокинезии, а также повышают потенциальные возможности структур, регулирующих лейкопоэз. Character of changes of leukopoiesis morphofunctional indeces under combined effect of hypokinesa and stevia in dynamics have been studied. It has been shown that biologically active compounds possessing pharmacotherapeutic properties contained in stevia leaves activate proliferation, differentiation and maturation of leukoblastic seedling cells, enhance potential possibility of regulating systems of leukopoiesis, contribute to negative effect prevention of hypokinesia.
Keywords: Medicine; Biology; Diseases of the blood and blood-forming organs; Therapeutics; Pharmacology